A Bourdieusian perspective on acculturation: Mexican immigrants in the United States - Leonel Prieto; Tagi Sagafi-nejad; Balaji Janamanchi (Administrative Sciences, 2013)
This article uses Bourdieu's theory of practice (BTOP) to understand immigrants' acculturation. It synthesizes research findings by discussing acculturation as: (1) equalization of immigrants' and natives' development (convergence); (2) language and social practices related to economic, cultural, social and symbolic capitals; and (3) relationships among acculturation indicators in the evolving interactions among immigrants' habituses and their economic, cultural, social, and symbolic capitals. Hypotheses tests use micro, meso and macro-level practices. Results confirm a systemic correspondence between the habitus and different types of capital, suggesting that relationships among components of immigrants' habituses and their capitals change as acculturation develops.
Keywords: 350; Bourdieu‘ s theory of practice; immigration; Mexican immigrants; United States; acculturation practices